Projeto de Malha de Captura de Fase Autocalibrável - Rui André Moutinho Teixeira (2018)
The impacts of process variations and intra-die device mismatches of analog and mixed-signal (AMS) circuits, namely regarding fabrication yield, costs, and reliability have become critical with the adoption of deep sub-micron MOS technologies. When in operation, circuits' sensitivity to environmental quantities, such as temperature, voltage, as well as interferences originating from other blocks, render new sources of variability. High performance circuits require the adoption of built-in calibration and test facilities which facilitate tuning performance parameters after fabrication and correcting them when in operation. This extra added circuitry may represent a small fraction of total circuit area and power, but still it may be more area- and power- efficient than either analog "overdesign" or purely digital detection and correction .